لترقية لدي الطلبة في المهارة الكلام ( Jigsaw ) طريقة تعليم جغسو - Banta Ali (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
Jigsaw Comparative learning method is one of the special methods in the concentration of various knowledge disciplines of today. The process of learning and teaching requires adjustment in applying various methods to achieve maximum educational goals. The purpose of education will never be achieved unless by applying the correct and effective method. Therefore,